Oxidative pyrolysis of Guadua angustifolia Kunth - C. R. Ardila; M. B. Folgueras; F. J. Fernández (Energy Reports, 2020)
This is a study of the behavior of the species of bamboo Guadua angustifolia Kunth during oxidative pyrolysis. Thus, thermogravimetric analysis of G. angustifolia combustion in an oxygen flow rate of 50 cm3/min and at a heating rate of 10 C/min was carried out. Moreover, the combustion profile was compared with the pyrolysis profile of G. angustifolia in nitrogen, using the same flow rate and the same heating rate. For this type of bamboo, devolatilization during combustion (oxidative pyrolysis) is boosted by the heterogeneous oxidation of the pyrolyzable fraction of this material. Therefore, the emission of volatiles is highly accelerated. This fact may be due to both the use of an oxygen flow and the inorganic composition of G. angustifolia, which contains high concentrations of potassium. This potassium may act as a catalyst that weakens organic matter bonds by an oxygen transfer mechanism. This behavior is not observed for all types of biomass. Therefore, it is likely that inorganic matter of biomass plays an important role in the way its oxidation occurs, which has a significant influence on the choice of the most suitable process for its valorization.
Keywords: 330; Inert pyrolysis; Kunth; Oxidative pyrolysis; Potassium; Thermogravimetric analysis